2021
DOI: 10.3389/frobt.2021.719944
|View full text |Cite
|
Sign up to set email alerts
|

On the Social-Relational Moral Standing of AI: An Empirical Study Using AI-Generated Art

Abstract: The moral standing of robots and artificial intelligence (AI) systems has become a widely debated topic by normative research. This discussion, however, has primarily focused on those systems developed for social functions, e.g., social robots. Given the increasing interdependence of society with nonsocial machines, examining how existing normative claims could be extended to specific disrupted sectors, such as the art industry, has become imperative. Inspired by the proposals to ground machines’ moral status … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(78 reference statements)
0
4
0
Order By: Relevance
“…Finally, the present study captured only two types of responses: support for AI art and negative beliefs about AI image generators taking jobs from artists and stealing their art styles. Future research could examine whether patterns in media use and exposure to specific media messages also predict other responses, including anthropomorphization of AI image generators, evaluations of AI artworks, and attributions of responsibility for AI art (see, e.g., Epstein et al 2020;Funk et al 2023;Hong and Curran 2019;Lima et al 2021;Mikalonytė and Kneer 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the present study captured only two types of responses: support for AI art and negative beliefs about AI image generators taking jobs from artists and stealing their art styles. Future research could examine whether patterns in media use and exposure to specific media messages also predict other responses, including anthropomorphization of AI image generators, evaluations of AI artworks, and attributions of responsibility for AI art (see, e.g., Epstein et al 2020;Funk et al 2023;Hong and Curran 2019;Lima et al 2021;Mikalonytė and Kneer 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the explosion of broad popular interest in these technologies, one experimental study found that varying the valence (positive or negative) and agency language (agent or tool) in information about AI image generators influenced the extent to which participants anthropomorphized such generators as well as the degree of credit for AI art they attributed to different actors (Epstein et al 2020). Studies have also explored how participants evaluate AI art and AI image generators after viewing the former or interacting with the latter (Gu and Li 2022;Hong and Curran 2019;Lima et al 2021;Mikalonytė and Kneer 2022). Looking at US public opinion more broadly, a national survey conducted by the Pew Research Center in December 2022 found that 20% of respondents saw "using artificial intelligence (AI) to produce visual images from keywords" as a "major advance for the visual arts," and another 26% saw it as a "minor advance" (Funk et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Images which had a significant level of detail were most frequently assumed to be made by human artists, while simple abstract images were assumed to be generated by AI. 5 In reality, all the images in the experiments were generated using a recent StyleGAN2 neural network model that was trained by the scientists on tens of thousands of historical paintings from the wikiart.org site.…”
Section: Art and Realismmentioning
confidence: 99%
“…Developing robust defences against such attacks and ensuring the security of AI systems are crucial challenges for the future. Collaboration and regulation also stand as critical challenges in the future of AI (Lima et al, 2021). AI is a global technology that transcends national borders, and ensuring responsible development and deployment necessitate international cooperation and consensus on ethical standards and legal frameworks.…”
Section: Introductionmentioning
confidence: 99%